Adaptive Level–Crossing Sampling Based DSP Systems - Baums, A.; Greitans, M.; Grunde, U. (Elektronika ir Elektrotechnika, 2009)
Adaptive level–crossing sampling based DSP systems are able to provide energy–efficient data acquisition and transmission. The proposed sampling mechanism is a generalization of the sampling with equidistantly spaced reference levels. Two different sampling implementations are offered. Simulation of the adaptive level–crossing sampling is performed to estimate the number of reference levels and evaluate the quality of signal reconstruction. The approach is targeting non–stationary and nonlinear signals using non–conventional digital signal processing methods. High correlation between input and reconstructed signal is supporting use of small number 9–16 sampling levels. Ill. 5, bibl. 13, tabl. 4 (in English; abstracts in English, Russian and Lithuanian).